INTERNATIONAL SITUATION AND EUROPEAN MISSIONS IN THE OTTOMAN EMPIRE: GERMANY AND GREAT BRITAIN(19th CENTURY) - Рахимова И. Х. (TARIXIY TADQIQOTLAR, 2026)
The article examines the main directions of diplomatic and military activities carried out by German and British missions in the Ottoman Empire during the 19th century. Special attention is given to the influence of the international situation, the growing rivalry among European powers in the Middle East, and the role of the Ottoman Empire within the system of international relations. The analysis shows that Great Britain sought to preserve the territorial integrity of the Ottoman Empire as a barrier against Russian expansion, whereas Germany strengthened its military and economic presence, making the region an important element of its eastern policy.